Battle Exhortations in Polybius - Hau, Lisa Irene (Classica et Mediaevalia, 2026)
This paper begins with considering the authenticity of Polybius’ battle exhortations in the light of Hansen’s well-known arguments for the impossibility of delivering speeches to a large body of deployed soldiers. For this purpose, the battle exhortations in Polybius are divided into categories depending on their delivery situation. This leads to the conclusion that many of the speeches must be fictional, but that battle exhortations are important for Polybius, and so begs the question of what function they fulfil in his Histories. In order to answer this question, the battle exhortations are divided into a different set of categories, depending on Polybius’ reporting style, i.e. whether the speech is reported in oratio recta, oratio obliqua, a combination of the two, is just briefly summarised, or is simply mentioned. The battle exhortations which are reported in oratio recta, oratio obliqua, or ‘combination mode’ are discussed in some detail before facing the question of why Polybius thought such speeches sufficiently important to include brief summaries or even briefer mentions of them even when he did not report them.